Difusi Inovasi dan Adopsi Inovasi 99design.com (Studi Kasus di Yayasan Pondok Pesantren Wahid Hasyim Yogyakarta) - Mohamad Hasan As'adi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
The development of communication technology made 99design.com born as the largest graphic design market in the world. With the limitations of information and communication technology as well as the internet in the village, the process of developing the diffusion of innovation continues slowly and steadily. This study aims to determine the diffusion of innovation and innovation adoption of 99design.com at the Wahid Hasyim Yogyakarta Islamic Boarding School Foundation. The method used in this study is a qualitative method with in-depth interviews and observation in data collection. The results of this study reveal that the diffusion process in this case includes four elements, namely, innovation, means and channels of communication, timeframe, and members of the social system running well. As an innovation, 99design.com also fulfills the five characteristics of an innovation so that it is easy to adopt, namely relative advantages, compatibility, complexity, triability, and observability. Some of the communication channels include mass communication in the form of village designer documentaries, group chat group communication and social media, and interpersonal communication channels by means of counseling with a relatively long time.